In Celiac Disease Patients the In Vivo Challenge with the Diploid Triticum monococcum Elicits a Reduced Immune Response Compared to Hexaploid Wheat. Issue 11 (18th May 2020) - Picascia, Stefania; Camarca, Alessandra; Malamisura, Monica; Mandile, Roberta; Galatola, Martina; Cielo, Donatella; Gazza, Laura; Mamone, Gianfranco; Auricchio, Salvatore; Troncone, Riccardo; Greco, Luigi; Auricchio, Renata; et al.
Abstract : Scope: Gluten from the diploid wheat Triticum monococcum (TM) has low content of immunostimulatory sequences and a high gastro‐intestinal digestibility. Gluten‐reactive T cells elicited by diploid and hexaploid ( Triticum aestivum ‐TA) wheat in celiac disease (CD) patients upon a brief oral challenge are analyzed. Methods and results: Seventeen patients with CD (median age 13 years) consumed for 3 days sandwiches made with TM (cultivar Norberto‐ID331, N =11), or TA (cultivar Sagittario, N =11) flours, corresponding to 12 gr of gluten/die. Immunostimulatory properties are assessed in blood by measuring the IFN‐γ‐secreting T cells by EliSpot and the expression of inflammatory cytokines/receptors (IL‐12A, IL‐15, IL‐18RAP, IFN‐γ) by qPCR. TA mobilizes a remarkable number of gliadin‐specific, IFN‐γ‐secreting T cells ( p <0.05), while no significant cell mobilization is induced by TM ( p =ns). Similar results are obtained in response to five immunogenic peptides from α‐, ω‐, and γ‐gliadins, although with a large individual variability. An increased mRNA expression for IL‐12A and IFN‐γ is detected in the group eating TA compared to those consuming TM ( p <0.05). Conclusions: Although T. monococcum is a cereal not suitable for the diet of celiacs, this diploid wheat elicits a reduced in vivo T‐cell response compared to T . aestivum in celiac patients. Abstract : The in vivo immunogenicity of Triticum monococcum (TM) and Triticum aestivum (TA) wheats is assessed in celiacs after 3 days of bread consumption. TM mobilizes a reduced number of IFN‐γ‐secreting‐T cells, and elicits a reduced IL‐12A and IFN‐γ mRNA expression compared to TA ( p <0.05). No differences are detected in the expression of IL‐15, IL‐18RAP among the two groups of patients.